2022
DOI: 10.1007/s40801-022-00331-5
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Research Studies Using Data from the Administrative Claims Databases in Japan

Abstract: Background In Japan, several research studies have used administrative claims databases. However, no study has compared the studies conducted in each database. Objective We assessed the type, design, and research area of each research study using the administrative databases in Japan to illustrate the suitability of the database used for the types of research studies. Methods We reviewed studies from four administrative claims databases (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Nevertheless, there are some limitations. First, although information on participants was based on a database of a Japan-supported social insurance organization and health checkups [23], selection bias should be of concern since the participants were employees of various companies and some of their dependents. Moreover, only participants who underwent physical examinations accompanied by blood tests were included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are some limitations. First, although information on participants was based on a database of a Japan-supported social insurance organization and health checkups [23], selection bias should be of concern since the participants were employees of various companies and some of their dependents. Moreover, only participants who underwent physical examinations accompanied by blood tests were included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this subsection, we compare this review with 2 similar studies [ 27 , 28 ]. Hirose et al [ 27 ] conducted a narrative review of 68 studies on the secondary use of claims data in a specific database, NDB, from October 2016 to June 2019.…”
Section: Discussionmentioning
confidence: 99%
“…They summarized 5 key pieces of information, including study design, research area, setting or sample, outcomes, and strengths and limitations. Subsequently, Fujinaga and Fukuoka [ 28 ] conducted a similar narrative review of 643 studies on the secondary use of claims data in 4 large-scale domestic databases: NDB, DPC database (MHLW), JMDC, and MDV, from January 2015 to October 2020, from which 3 categories of research type, design, and area were analyzed descriptively. Both studies used a classification of the journals in which the target articles were published to extract information about the research area [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the level of information on confounders available in the data and the study design, methods such as instrumental variable (IV) methods [ 61 ], difference-in-difference [ 62 ], missing cause [ 63 ], trend-in-trend [ 64 ], and perturbation variable [ 65 ] may be appropriate. Studies using Japanese databases with such quasi-experimental designs accounted for 22.1% (142/643) of all the studies using RWD reported from 2015 to 2020 [ 7 ]. Few Japanese studies used quasi-experimental designs other than propensity score methods.…”
Section: Challenges and Solutions Relating To The Methodologymentioning
confidence: 99%
“…Most studies using RWD from MDV and JMDC focus on describing patient characteristics and treatment patterns since such RWD sources contain little information on clinical characteristics and outcomes [ 4 ]. A recent review that assessed the types of studies conducted between 2015 and 2020 using claims databases in Japan found that descriptive studies were the most common, accounting for 63%, 43%, and 41% of the studies conducted using NDB, MDV, and JMDC data, respectively [ 7 ]. To address this issue of missing data and to create a high-quality medical information database for conducting rigorous assessments of drug safety, the Medical Information Database Network (MID-NET) was launched in April 2018, in collaboration with 23 hospitals from 10 healthcare organizations across Japan.…”
Section: Introductionmentioning
confidence: 99%